A progressive damage model of textile composites on meso-scale using finite element method: Fatigue damage analysis. (May 2015) - Xu, J.; Lomov, S.V.; Verpoest, I.; Daggumati, S.; Van Paepegem, W.; Degrieck, J.
Highlights: A FE approach for progressive fatigue damage in textile composites on fabric unit cell is proposed. S–N curves of UDs out of fatigue tests in four directions are used as input for the impregnated yarns. Multi-axial fatigue is applied to matrix-rich direction; fibre fatigue is separately treated. Continuum damage mechanics method is used to describe the properties' deterioration. The numerical results agree well with experiments. Abstract: A finite element (FE) approach for tension–tension fatigue damage in textile reinforced composites on meso-scale level (fabric unit cell) is proposed. S–N curves of a unidirectional composite (UD) out of the fatigue tests in fibre, transverse-fibre, in-plane-shear and out-of-plane-shear directions are used as the input for the impregnated yarns. The algorithm of multi-axial fatigue is applied to matrix-dominated fatigue, while the fibre-dominated fatigue is separately considered. The continuum damage mechanics method is used to describe the properties' deterioration. The stress redistribution introduced by stiffness degradation conjugates the damage evolution. Averaged mechanical properties of the unit cell in pre- and post-fatigue damage stages are calculated at predefined load cycle numbers, using a numerical homogenization technique. The numerical results are validated by experiments of two types of carbon/epoxy plain weave composites, which have the same fibre/resin system but different textile structures. The validation showed good agreement between modelling and experiment.